Ceramic modified lithium battery diaphragm and preparation method thereof

By using ceramic modified materials and specific preparation methods in the lithium battery separator to form a mesh structure, the problem of insufficient wetting and heat resistance of the existing separator is solved, and the overall performance and safety of the lithium battery is significantly improved.

CN119208902APending Publication Date: 2024-12-27HEBEI GELLEC NEW ENERGY MATERIAL SCI&TECHNOLOY CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411300796.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-18
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The infiltration performance and heat resistance of existing lithium battery separators limit the transmission of lithium ions in the pores and affect the overall performance and safety of the battery.

Method used

A ceramic-modified lithium battery separator, including a base film and coating, contains ceramic powder, modified resin, nanocellulose crystals and coating agent, and is coated and secondary by a specific slurry preparation method. Coating, forming a mesh structure to improve the heat resistance and wetting ability of the diaphragm.

Benefits of technology

It significantly improves the heat resistance, wetting ability and liquid retention rate of the diaphragm, forms a stable structure, and enhances the overall performance and safety of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119208902A_ABST
    Figure CN119208902A_ABST
Patent Text Reader

Abstract

The invention discloses a ceramic modified lithium battery diaphragm and a preparation method thereof, the ceramic modified lithium battery diaphragm comprises a base membrane and a coating on the base membrane, and the coating comprises ceramic powder, modified resin, nano cellulose crystals and a coating agent. The modified resin is epoxy resin, and the coating agent is N-phenylmaleimide. The preparation method comprises the following steps: firstly, coating a base membrane with slurry containing ceramic powder and modified resin, and then carrying out secondary coating by adopting a coating solution, so as to obtain the ceramic modified lithium battery diaphragm which takes the ceramic powder as a substrate, and the modified resin and the coating agent in the coating solution are crosslinked into a net structure to be attached to the substrate. The heat-resistant effect, the infiltration capacity and the liquid retention rate of the diaphragm can be effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of battery separators, and in particular relates to a ceramic-modified lithium battery separator and a preparation method thereof. Background Art

[0002] As environmental problems become increasingly severe, more and more new energy projects have attracted social attention, among which electric vehicles are particularly popular. As the power source of electric vehicles, lithium-ion batteries are the focus of scientific research on safety and endurance. As one of the key inner components of ion batteries, the diaphragm absorbs electrolyte to prevent short circuits while allowing ion conduction. When overcharged or the temperature rises, the diaphragm blocks current conduction through closed pores to prevent explosion. However, the diaphragm has poor wettability, which limits the transmission of lithium ions in the pores of the diaphragm, thus affecting the overall performance of the battery. Both wettability and thermal shrinkage are important indicators for characterizing diaphragms, and are also important properties related to battery safety.

[0003] Lithium battery separators are crucial in lithium batteries. Conventional alumina or boehmite coated separators have average wettability and heat resistance and cannot meet the above requirements. Summary of the invention

[0004] In view of the deficiencies of the prior art, an object of the present invention is to provide a ceramic-modified lithium battery separator.

[0005] Another object of the present invention is to provide a method for preparing the above-mentioned ceramic-modified lithium battery separator.

[0006] Another object of the present invention is to provide a slurry.

[0007] Another object of the present invention is to provide a method for preparing the slurry.

[0008] The purpose of the present invention is achieved through the following technical solutions.

[0009] A ceramic-modified lithium battery separator comprises: a base film and a coating on the base film, wherein the coating comprises: ceramic powder, modified resin, nanocellulose crystals (CNC) and a coating agent, and the ratio of the ceramic powder, modified resin, nanocellulose crystals (CNC) and the coating agent is (7-10):(5-7.5):(0.05-0.1):(5-10) by mass.

[0010] In the above technical solution, the ceramic-modified lithium battery separator also includes: a dispersant and an adhesive. In terms of mass fractions, the ratio of the ceramic powder, the dispersant and the adhesive is (7-10): (0.05-0.2): (5-10).

[0011] In the above technical solution, the modified resin is one or a mixture of epoxy resin, acrylic resin, polyimide resin, phenolic resin, bismaleimide resin, silicone resin, cyanate resin, polyetheretherketone resin, polyphenylene sulfide resin, polyphenylsulfone resin, polyethersulfone resin and polyetherimide resin.

[0012] In the above technical solution, the modified resin is preferably epoxy resin.

[0013] In the above technical solution, the density of the epoxy resin is 1.05-1.40 g / cm 3 , appearance is yellow or transparent solid.

[0014] In the above technical solution, the ceramic powder is alumina and / or boehmite.

[0015] In the above technical solution, the coating agent is one or a mixture of N-phenylmaleimide, tributyl phosphate, N-methylpyrrolidone, methyl isobutyl ketone and dioctyl sulfoxide.

[0016] In the above technical solution, the coating agent is preferably N-phenylmaleimide.

[0017] In the above technical solution, the boiling point of the N-phenylmaleimide is 162-163°C and the density is 1.2427 g / cm 3 It has the appearance of yellow needle-shaped crystals, a flash point of 162-163°C, and a molecular weight of 173.17.

[0018] The preparation method of the above-mentioned ceramic modified lithium battery separator comprises: coating the slurry on the base film, drying to obtain the ceramic modified lithium battery separator precursor, secondary coating the ceramic modified lithium battery separator precursor with a coating liquid, extracting, and drying to obtain the ceramic modified lithium battery separator, wherein the coating liquid is a mixture of a coating agent and a solvent.

[0019] In the above technical solution, the solvent is ethyl acetate.

[0020] In the above technical solution, the concentration of the coating agent in the coating liquid is 75-99wt%.

[0021] In the above technical solution, the loading amount of the slurry on the ceramic-modified lithium battery separator precursor is 3.5-4.5 g / ㎡, and the loading amount of the slurry and the coating liquid on the ceramic-modified lithium battery separator is 4.8-6.0 g / ㎡.

[0022] In the above technical solution, the extractant is ethyl acetate.

[0023] A slurry comprises: ceramic powder, modified resin and nano cellulose crystals (CNC), wherein, by weight, the ratio of the ceramic powder, modified resin and nano cellulose crystals (CNC) is (7-10): (5-7.5): (0.05-0.1).

[0024] The above technical solution also includes: a dispersant, water and an adhesive. In terms of mass fractions, the ratio of the ceramic powder, the dispersant, water and the adhesive is (7-10): (0.05-0.2): (20-25): (5-10).

[0025] In the above technical solution, the adhesive is polyacrylate.

[0026] In the above technical solution, the dispersant is an ammonium salt dispersant.

[0027] The method for preparing the above slurry comprises the following steps:

[0028] Step 1, mixing ceramic powder, modified resin and nanocellulose crystal (CNC) suspension until uniform, filtering, and drying to obtain a first powder, wherein the ratio of the ceramic powder, modified resin and nanocellulose crystal (CNC) in the nanocellulose crystal (CNC) suspension is (7-10): (5-7.5): (0.05-0.1) by mass;

[0029] In step 1, ceramic powder, modified resin and nanocellulose crystal (CNC) suspension are mixed and stirred at room temperature for 10 to 30 minutes until uniform.

[0030] In step 1, drying is performed until the moisture content is 0.6-0.8% (mass fraction).

[0031] In step 1, the particle size of the first powder is 400-500 nm.

[0032] In step 1, the density of nanocellulose crystals (CNC) was 1.05 g / cm 3 The width of the nanocellulose crystal (CNC) is 4 to 5 nm, and the length of the nanocellulose crystal (CNC) is 50 to 500 nm.

[0033] In step 1, the nanocellulose crystal (CNC) suspension is a mixture of nanocellulose crystal (CNC) and water, and the content of nanocellulose crystal (CNC) in the nanocellulose crystal (CNC) suspension is 5-10 wt%.

[0034] Step 2, mixing the first powder, dispersant, water and adhesive until uniform to obtain a slurry, wherein the ratio of the ceramic powder, dispersant, water and adhesive is (7-10):(0.05-0.2):(20-25):(5-10) by mass.

[0035] In step 2, the first powder, dispersant and water are first mixed until uniform to obtain a first solution, and then the first solution and adhesive are mixed until uniform to obtain the slurry.

[0036] In step 2, the first powder, dispersant and water are mixed, first stirred at a rotation speed of 3100-3600 r / min and a revolution speed of 10-20 r / min for 10-30 min, and then ultrasonicated at a frequency of 5-7 kHz for 10-30 min until uniform, to obtain a first solution.

[0037] In step 2, the first solution and the adhesive are mixed, first stirred at a rotation speed of 1000-2000 r / min and a revolution speed of 15-20 r / min for 5-10 min, and then ultrasonicated at a frequency of 5-7 kHz for 10-15 min until uniform.

[0038] In step 2, the grinding speed is 400-650 r / min, and the grinding time is 10-15 min.

[0039] Compared with the prior art, the present invention has the following beneficial effects:

[0040] The present invention first coats a slurry containing ceramic powder and modified resin on a base film, and then uses a coating liquid for secondary coating to obtain a ceramic-modified lithium battery separator with ceramic powder as the base, the modified resin and the coating agent in the coating liquid being cross-linked into a network structure attached to the base, and the nanocellulose crystals in the slurry provide a skeleton support to form a stable structure, which can effectively improve the heat resistance, wetting ability and liquid retention rate of the separator. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 This is a distribution diagram of the ceramic-modified lithium battery separator prepared in Example 1 under a scanning electron microscope;

[0042] Figure 2 This is a distribution diagram of the ceramic-modified lithium battery separator prepared in Comparative Example 1 under electron microscope scanning;

[0043] Figure 3 This is the distribution diagram of the lithium battery separator without surface modification prepared in Comparative Example 2 under electron microscope scanning. DETAILED DESCRIPTION

[0044] The technical solution of the present invention is further described below in conjunction with specific embodiments.

[0045] N-phenylmaleimide crystallized from cyclohexane (or benzene) is light yellow needle-shaped crystal. It is insoluble in water and petroleum ether, soluble in general organic solvents, especially soluble in acetone, ethyl acetate and benzene. It is stable at room temperature and pressure, avoid contact with oxides, keep the container sealed, and store in a cool and dry place.

[0046] Epoxy resin is a high molecular polymer with the molecular formula (C 11 H 12 O3)n is a general term for a class of polymers containing more than two epoxy groups in the molecule. It is a condensation product of epichlorohydrin and bisphenol A or polyols. Due to the chemical activity of the epoxy group, it can be opened with a variety of compounds containing active hydrogen, cured and cross-linked to form a network structure, so it is a thermosetting resin.

[0047] Aluminum oxide is an inorganic substance with the chemical formula Al2O3. It is a high-hardness compound with a melting point of 2054°C and a boiling point of 2980°C. It is an ionized crystal that can be ionized at high temperatures and is often used to make refractory materials.

[0048] Liquid retention rate and liquid absorption rate: Cut the diaphragm into samples with a width of 30 mm and a length of 100 mm, weigh them and record them as the mass before immersion (m0), soak them in an electrolyte at 20-25°C for 30 minutes, take them out and weigh them as the mass after immersion (m1), and then place them at 20-25°C for 1 hour, weigh the mass and record it as m2, calculate the liquid retention rate and liquid absorption rate: liquid retention rate = (m2-m0) / m0, liquid absorption rate = (m1-m0) / m0.

[0049] In the tests of liquid absorption rate and liquid retention rate, the diaphragm is one of the ceramic-modified lithium battery diaphragms prepared in Examples 1 to 3, the ceramic-modified lithium battery diaphragm prepared in Comparative Example 1, the lithium battery diaphragm without surface modification prepared in Comparative Example 2, and the lithium battery diaphragm prepared in Comparative Example 3.

[0050] In the following examples, water is deionized water.

[0051] In the following examples, the base film is a PE film, and the thickness of the base film is 7 μm.

[0052] The electrolyte used in the present invention is a mixture of an electrolyte and a solvent, the electrolyte in the electrolyte is LiPF6, the solvent is a mixture of ethylene carbonate (EC) and dimethyl carbonate, the concentration of the electrolyte in the electrolyte is 1 mol / L, and the volume ratio of ethylene carbonate to dimethyl carbonate is 1:1.

[0053] Example 1

[0054] A preparation method of a ceramic modified lithium battery separator comprises: coating a slurry on a base film by roller coating (anilox roller), drying at 100° C. for 20 seconds to obtain a ceramic modified lithium battery separator precursor, coating a coating liquid on the ceramic modified lithium battery separator precursor by roller coating (anilox roller) (secondary coating) and extracting (the coating liquid is placed in a material tank where the anilox roller is located, and the extractant is placed in the extraction tank), and drying at 90° C. for 20 seconds to obtain a ceramic modified lithium battery separator, wherein the coating liquid is a mixture of a coating agent and a solvent, the coating agent is N-phenylmaleimide, the solvent is ethyl acetate, the concentration of the coating agent in the coating liquid is 98wt%, the boiling point of N-phenylmaleimide is 162-163° C., and the density is 1.2427 g / cm 3 The appearance is yellow needle-shaped crystals, the flash point is 162-163°C, and the molecular weight is 173.17. The loading amount of the slurry on the ceramic-modified lithium battery separator precursor is 4.5 g / ㎡, and the loading amount of the slurry and the coating liquid on the ceramic-modified lithium battery separator is 5.5 g / ㎡. The extractant is ethyl acetate (to extract impurities).

[0055] The method for preparing the slurry in Example 1 comprises the following steps:

[0056] Step 1: In a reaction kettle, ceramic powder, modified resin and nanocellulose crystal (CNC) suspension are mixed, stirred at 25° C. for 30 min until uniform, filtered (filter pressed), dried to a moisture content of 0.8% (mass fraction), crushed, and sieved to obtain a first powder with a particle size of 400-500 nm, wherein the ratio of ceramic powder, modified resin and nanocellulose crystal (CNC) in the suspension is 10:7.5:0.1 by mass, the modified resin is epoxy resin, and the density of the epoxy resin is 1.2 g / cm 3 The appearance is yellow or transparent solid. The ceramic powder is aluminum oxide. The nanocellulose crystal (CNC) suspension is a mixture of nanocellulose crystal (CNC) and water. The content of nanocellulose crystal (CNC) in the nanocellulose crystal (CNC) suspension is 5wt%, and the density of nanocellulose crystal (CNC) is 1.05g / cm 3 , the width of nanocellulose crystal (CNC) is 4-5 nm, and the length of nanocellulose crystal (CNC) is 50-500 nm;

[0057] Step 2, mixing the first powder, the dispersant and the water, stirring for 10 minutes at a rotation speed of 3100 r / min and a revolution speed of 20 r / min in a planetary stirring device, and then ultrasonicating for 10 minutes at a frequency of 5 kHz in an ultrasonic device until uniform, to obtain a first solution, mixing the first solution and the adhesive, stirring for 30 minutes at a rotation speed of 1000 r / min and a revolution speed of 20 r / min in a planetary stirring device, and then ultrasonicating for 15 minutes at a frequency of 5 kHz until uniform, putting into a grinder, grinding at a speed of 650 r / min for 10 minutes, to obtain a slurry, wherein, by mass, the ratio of ceramic powder, dispersant, water and adhesive is 10:0.2:25:5, the adhesive is polymethyl acrylate, and the dispersant is an ammonium salt dispersant (ammonium polyacrylate).

[0058] The ceramic-modified lithium battery separator prepared in Example 1 is based on ceramic powder (alumina), and the modified resin (epoxy resin) is cross-linked with the coating agent in the coating liquid to form a network structure attached to the substrate.

[0059] Example 2

[0060] A method for preparing a ceramic-modified lithium battery separator is basically the same as Example 1 "A method for preparing a ceramic-modified lithium battery separator", with the only difference being that "epoxy resin" is replaced by "acrylic resin".

[0061] The ceramic-modified lithium battery separator prepared in Example 2 is based on ceramic powder (alumina), and the modified resin (acrylic resin) is cross-linked with the coating agent in the coating liquid to form a network structure attached to the substrate.

[0062] Example 3

[0063] A method for preparing a ceramic-modified lithium battery separator is basically the same as Example 1 "A method for preparing a ceramic-modified lithium battery separator", with the only difference being that "epoxy resin" is replaced by "polyimide resin".

[0064] The ceramic-modified lithium battery separator prepared in Example 3 is based on ceramic powder (alumina), and the modified resin (polyimide resin) is cross-linked with the coating agent in the coating liquid to form a network structure attached to the substrate.

[0065] Comparative Example 1

[0066] A method for preparing a ceramic-modified lithium battery separator is basically the same as Example 1 "A method for preparing a ceramic-modified lithium battery separator", with the only difference being that "the coating liquid is a mixture of a coating agent and a solvent, the coating agent is N-phenylmaleimide, and the solvent is ethyl acetate" is replaced with "the coating liquid is ethyl acetate".

[0067] Comparative Example 2

[0068] A method for preparing a lithium battery separator without surface modification is basically the same as Example 1 "a method for preparing a ceramic-modified lithium battery separator", and the only difference is that the slurry is different.

[0069] The preparation method of the slurry in Comparative Example 2 includes: mixing alumina (particles), a dispersant and water, stirring for 10 minutes at a rotation speed of 3100 r / min and a revolution speed of 20 r / min in a planetary stirring device, and then ultrasonicating for 10 minutes at a frequency of 5 kHz in an ultrasonic device until uniform to obtain a solution A, mixing the solution A and an adhesive, stirring for 30 minutes at a rotation speed of 1000 r / min and a revolution speed of 20 r / min in a planetary stirring device, and then ultrasonicating for 15 minutes at a frequency of 5 kHz until uniform, putting into a grinder, and grinding at a speed of 650 r / min for 10 minutes to obtain a slurry, wherein, by mass, the ratio of alumina, dispersant, water and adhesive is 15:0.2:79.8:5, the adhesive is polymethyl acrylate, and the dispersant is an ammonium salt dispersant (ammonium polyacrylate).

[0070] Comparative Example 3

[0071] A method for preparing a lithium battery separator comprises: coating a slurry on a base film by roller coating (anilox roller), and drying at 100° C. for 20 seconds to obtain a lithium battery separator. The method for preparing the slurry in Comparative Example 3 comprises: mixing the first powder prepared in Example 1, a dispersant, water and N-phenylmaleimide (the same as the N-phenylmaleimide in Example 1), stirring for 10 minutes at a rotation speed of 3100 r / min and a revolution speed of 20 r / min in a planetary stirring device, and then ultrasonicating at a frequency of 5 kHz for 10 minutes until uniform to obtain a B solution, mixing the B solution and an adhesive, and first stirring at 1000 r / min in a planetary stirring device. The mixture was stirred at a rotation speed of 1000 r / min and an orbital speed of 20 r / min for 30 min, then ultrasonicated at a frequency of 5 kHz for 15 min until uniform, put into a grinder, and ground at a speed of 650 r / min for 10 min to obtain a slurry, wherein, by mass, the ratio of ceramic powder, dispersant, water, N-phenylmaleimide and adhesive in the first powder is 17.5:0.2:25:5:5, the adhesive is polymethyl acrylate, and the dispersant is polyacrylate ammonium salt.

[0072] The ceramic-modified lithium battery separators prepared in Examples 1 to 3, Comparative Example 1, the lithium battery separators without surface modification prepared in Comparative Example 2, and the lithium battery separators prepared in Comparative Example 3 were tested. The test conditions were all carried out under standard atmospheric conditions, i.e., temperature: 20-25°C; relative humidity: 50-65%; atmospheric pressure: 90-100 kPa. The test results are shown in Table 1.

[0073] Table 1

[0074]

[0075] As shown in Table 1, the heat resistance of the ceramic modified lithium battery separator prepared in Examples 1 to 3 is the best. It can be seen that the ceramic modified lithium battery separator prepared by using the slurry modified by the surface of aluminum oxide and epoxy resin combined with secondary coating has a more stable structure and better dispersion. The solid particles can be well maintained, the coating is uniform, the surface is flat, and no vertical scratches will appear. The slurries in Examples 1 to 3 were placed for 12 and 24 hours. It was not easy to precipitate or agglomerate by naked eye observation, and the storage stability was good.

[0076] Contact angle tests were performed on Examples 1 to 3, the ceramic-modified lithium battery separators prepared in Comparative Example 1, the lithium battery separators without surface modification prepared in Comparative Example 2, and the lithium battery separators prepared in Comparative Example 3. The results are shown in Table 2.

[0077] Table 2

[0078]

[0079]

[0080] It can be seen from Table 2 that the contact angle of the lithium battery separator without surface modification prepared in Comparative Example 2 is larger than that in Comparative Example 1. It can be seen that the wettability of the ceramic modified lithium battery separator prepared in Comparative Example 1 using ethyl acetate as the coating liquid is better than that of the lithium battery separator without surface modification, while the contact angles of the ceramic modified lithium battery separators prepared in Examples 1 to 3 of the present invention are all smaller than those of the comparative example, indicating that the wettability of the ceramic modified lithium battery separators prepared in Examples 1 to 3 of the present invention is better than that of the comparative example.

[0081] The liquid absorption rate and liquid retention rate of Examples 1 to 3, the ceramic modified lithium battery separator prepared in Comparative Example 1, the lithium battery separator without surface modification prepared in Comparative Example 2, and the lithium battery separator prepared in Comparative Example 3 were tested, and the results are shown in Table 3 (three parallel experiments were conducted for each example and comparative example).

[0082] Table 3

[0083]

[0084] It can be seen from Table 3 that the liquid absorption rate and liquid retention rate of the ceramic modified lithium battery separator prepared in Examples 1 to 3 of the present invention are greater than those of the comparative example, which further illustrates that the ceramic modified lithium battery separator prepared in Examples 1 to 3 of the present invention has better wetting ability.

[0085] Example 1 Test parameters of the ceramic-modified lithium battery separator prepared:

[0086]

[0087] Figure 1 This is the distribution diagram of the ceramic-modified lithium battery separator prepared in Example 1 under electron microscope scanning. Figure 2 This is the distribution diagram of the ceramic-modified lithium battery separator prepared in Comparative Example 1 under electron microscope scanning. Figure 3 This is the distribution diagram of the lithium battery separator without surface modification prepared in Comparative Example 2 under electron microscope scanning. Figure 1 to Figure 3 It can be seen that the ceramic-modified lithium battery separator prepared in Example 1 has a denser structure and can effectively improve the thermal shrinkage effect.

[0088] The present invention is described above by way of example. It should be noted that, without departing from the core of the present invention, any simple deformation, modification or other equivalent replacement that can be made by those skilled in the art without inventive effort falls within the protection scope of the present invention.

Claims

1. A ceramic-modified lithium battery separator, characterized in that: include: A base film and a coating on the base film, wherein the coating comprises: ceramic powder, modified resin, nanocellulose crystals and a coating agent, wherein the ratio of the ceramic powder, modified resin, nanocellulose crystals and coating agent is (7-10):(5-7.5):(0.05-0.1):(5-10) by mass, wherein the modified resin is one or a mixture of epoxy resin, acrylic resin, polyimide resin, phenolic resin, bismaleimide resin, silicone resin, cyanate resin, polyetheretherketone resin, polyphenylene sulfide resin, polyphenylsulfone resin, polyethersulfone resin and polyetherimide resin, and the coating agent is one or a mixture of several of N-phenylmaleimide, tributyl phosphate, N-methylpyrrolidone, methyl isobutyl ketone and dioctyl sulfoxide.

2. The ceramic-modified lithium battery separator according to claim 1, characterized in that: The ceramic-modified lithium battery separator also includes: a dispersant and an adhesive. Calculated by weight, the ratio of the ceramic powder, the dispersant and the adhesive is (7-10): (0.05-0.2): (5-10).

3. The ceramic-modified lithium battery separator according to claim 1, characterized in that: The ceramic powder is alumina and / or boehmite.

4. The ceramic-modified lithium battery separator according to claim 1, characterized in that: The width of the nanocellulose crystal is 4 to 5 nm, and the length of the nanocellulose crystal is 50 to 500 nm.

5. The method for preparing a ceramic-modified lithium battery separator according to any one of claims 1 to 4, characterized in that: include: The slurry is coated on the base film and dried to obtain a ceramic-modified lithium battery separator precursor. The ceramic-modified lithium battery separator precursor is secondarily coated with a coating liquid, extracted, and dried to obtain a ceramic-modified lithium battery separator. The coating liquid is a mixture of a coating agent and a solvent.

6. The preparation method according to claim 5, characterized in that: The concentration of the coating agent in the coating liquid is 75 to 99 wt %.

7. The preparation method according to claim 5, characterized in that: The loading amount of the slurry on the ceramic-modified lithium battery separator precursor is 3.5-4.5 g / ㎡, and the loading amount of the slurry and the coating liquid on the ceramic-modified lithium battery separator is 4.8-6.0 g / ㎡.

8. A slurry, characterized in that: include: Ceramic powder, modified resin and nano-cellulose crystals, wherein the ratio of the ceramic powder, modified resin and nano-cellulose crystals is (7-10):(5-7.5):(0.05-0.1) by mass.

9. A method for preparing a slurry, characterized in that: The following steps are involved: Step 1, mixing ceramic powder, modified resin and nanocellulose crystal suspension until uniform, filtering and drying to obtain a first powder, wherein the ratio of the ceramic powder, modified resin and nanocellulose crystals in the nanocellulose crystal suspension is (7-10): (5-7.5): (0.05-0.1) by mass; Step 2, mixing the first powder, dispersant, water and adhesive until uniform to obtain a slurry, wherein the ratio of the ceramic powder, dispersant, water and adhesive is (7-10):(0.05-0.2):(20-25):(5-10) by mass.

10. The method according to claim 9, characterized in that The nanocellulose crystal suspension is a mixture of nanocellulose crystals and water, and the content of the nanocellulose crystals in the nanocellulose crystal suspension is 5-10wt%.

Citation Information

Cited By

  • Diaphragm material for lithium battery and preparation method of diaphragm material

    CN120749353A